Wired/Wireless Internet Communications 8th International Conference, WWIC 2010, Lulea, Sweden, June 1-3, 2010. Proceedings - Osipov, Evgeny; Kassler, Andreas J.; Bohnert, Thomas Michael; Masip-Bruin, Xavier (Computer Communication Networks and Telecommunications, 2010)
Beginning with the first event in 2002, the International Conference on Wired/ Wireless Internet Communications (WWIC) has continuously been established as a highly selective conference focusing on integration and co-existence of rapidly dev- oping wireless network technologies and their applications related to the Internet. To do so WWIC provides an international forum for presenting and discussing cutti- edge research in this domain, and the 8th edition of WWIC, held at Luleå University in June 2010, continued this tradition. The WWIC 2010 call for papers attracted 45 submissions from more than 25 countries and each contribution was subject to thorough peer review by recognized int- national experts that acted as members of the Technical Program Committee. The selection process resulted in 16 accepted papers, which were thematically grouped into 5 technical sessions. The major themes of WWIC 2010 were cooperation, management of multimedia traffic, advancing IEEE 802.11, cognitive optimization, mesh and multi-hop networks, security, signaling, control, and wireless sensor networks.